Expressed Priorities of Assertiveness Trainess - Lefèvre, Esther R.; West, Malcolm L. (Canadian Journal of Counselling and Psychotherapy, 2011)
The assertion-related priorities of 84 English-speaking, Montréal trainees were assessed by having them rate their degree of interest in becoming more assertive in each of 26 major skill-areas. Consistent with previous American-based work (Cooley, 1979), trainees showed the most interest in learning how to deal with negative feelings in close, interpersonal relationships. In contrast, items which involved "saying no" to other people's requests were given low priority. A discrepancy between assertive skills usually emphasized in the professional, training literature and skills deemed most relevant by actual trainees was noted. Findings substantiate the importance of evaluating candidates' preferences for increased assertive skill before implementing assertiveness-training groups so as to better match program goals to participants' own self-expressed needs.